The sacrifice : a novel - Oates, Joyce Carol, 1938- (Ecco, an imprint of HarperCollinsPublishers, 2015)
When a fourteen-year-old girl is the alleged victim of a terrible act of racial violence, the incident shocks and galvanizes her community, exacerbating the racial tension that has been simmering in this New Jersey town for decades.